Efficacy of VEGFR-TKIs plus immune checkpoint inhibitors in metastatic renal cell carcinoma patients with favorable IMDC prognosis. (November 2021) - Ciccarese, C.; Iacovelli, R.; Porta, C.; Procopio, G.; Bria, E.; Astore, S.; Cannella, M.A.; Tortora, G.
Highlights: VEGFR-TKIs + PD-1 ICIs combinations are a new first-line standard of care in mRCC. The benefit of VEGFR-TKIs + ICIs is unclear in IMDC favorable mRCC patients. We performed a meta-analysis to assess VEGFR-TKIs + ICIs vs. sunitinib in IMDC favorable patients. VEGFR-TKI + ICI combinations improved PFS as first-line therapy. No OS advantage was observed in this subgroup. Abstract: Background: Combinations of PD-1/PD-L1 immune checkpoint inhibitors (ICI) with VEGFR-TKIs as first-line therapy significantly improve outcomes of metastatic renal cell carcinoma (mRCC) patients. The benefit of these combinations is well evident in the IMDC intermediate- and poor-risk population, but remains unclear in the subgroup of patients with favorable prognosis. Our meta-analysis aims at evaluating whether the addition of ICIs to VEGFR-TKIs is able to improve the outcome compared to VEGFR-TKIs alone in mRCC patients with favorable prognosis. Methods: This meta-analysis searched MEDLINE/PubMed, the Cochrane Library and ASCO Meeting abstracts for randomized clinical trials (RCTs) testing the combination of VEGFR-TKI + ICI in mRCC. Data extraction was conducted according to the PRISMA statement. Summary hazard ratio (HR) was calculated using random- or fixed-effects models, depending on studies heterogeneity. Results: Four RCTs were selected. VEGFR-TKI + ICI combinations improved PFS compared to sunitinib (fixed-effect, HR = 0.63; p < 0.00001). However, VEGFR-TKI + ICI combinations did not significantly prolong OS (fixed-effect; HR = 0.99; 95% CI 0.74–1.33; p = 0.95). Conclusion: VEGFR-TKI + ICI combinations improved PFS but not OS as first-line therapy for mRCC patients with favorable IMDC prognosis. Longer follow-up and further studies will increase the power of our analysis, suggesting the best first-line therapy for mRCC patients with favorable prognosis.